Analisis Sentimen Penggunaan Tol Trans Jawa Periode Mudik Lebaran 2019 dengan Metode K-Nearest Neighbor dan Seleksi Fitur Information Gain - Ahmad Fauzan Rahman; Indriati Indriati; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
One of the facilities provided by the government to speed up travel time is the toll road. Toll roads can also be referred to as highways that are connected from one city to another for four or more wheeled vehicles. In December 2018, the Trans Java Toll Road officially connected the two major cities in Indonesia, Jakarta and Surabaya. The new Trans Java Toll Road can be used in the period of eid 2019 will generate various opinions from its users. Many people in Indonesia use social media as one of the media to express their opinions. Thus this study tries to analyze public opinion on social media to be classified into two classes, namely positive and negative classes. The method used in this research is K-Nearest Neighbor with Information Gain Feature Selection. The classification process consists of preprocessing text including data cleansing, case folding, stop word removal, stemming and tokenization, term wighting with tf-idf, feature selection using Information Gain and classification using K-Nearest Neighbor. Tests in this study using confusion matrix produce accuracy of 85%, precision of 85%, recall of 100%, and f-measure of 91.89%.